La asistencia integral de enfermería y su relación con la condición de salud de los adultos mayores atendidos en las unidades operativas de la zona urbana de Riobamba, periodo Abril – Agosto 2011. - Cando, Adriana (2012)
This research entitled "Factors associated with resilience and its relationship with the family in high school adolescents Industrial Technical College Punin Condorazo of the parish in the period from January to June of 2012" was conducted to determine the factors that promote resilience in high school adolescents. The methodology was based on the systematic aspects of the scientific method and the techniques and instruments of valid research results obtained with these effective to obtain the required information.In this research, we worked with the universe that are 50 high school teenagers between 13 and 18 years of age, data were obtained through a questionnaire in which it was determined that behavioral and emotional factors enhance the resilience of adolescents , proceeded to the tabulation of data using tables and graphs with their analysis.